Results on Northern hake Spanish discard sampling programme - Pérez-Contreras, María Nélida; Araujo-Fernández, María Hortensia; Fernández-Llana, Carmen (2010)
Quarterly discards estimates for the Spanish bottom otter trawl fleet fishing in the Northeast Atlantic ICES Subareas VI and VII are presented for hake (Merluccius merluccius). Information was obtained by observers on board under different discard sampling programmes carried out by the Spanish research institute IEO. Raising based on effort (number of trips) was used to estimate total quarterly discards in weight and number for the fleet. Discards length distributions are also presented. Both in terms of weight and numbers discards present high variation in time, ranging from 0 to 1100 tonnes and from 0 to 12 million fish. Length distributions of discarded hake show that most of the individuals are juvenile fish, although some individuals above the minimum landing size (27 cm) are also discarded. Increases in the number of juveniles discarded are evident after year 2003.